The role of PD-1/PD-L1 axis in idiopathic pulmonary fibrosis: Friend or foe? - Jiang, Aimin; Liu, Na; Wang, Jingjing; Zheng, Xiaoqiang; Ren, Mengdi; Zhang, Wei; Yao, Yu (Frontiers in Immunology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a devastating interstitial lung disease with a bleak prognosis. Mounting evidence suggests that IPF shares bio-molecular similarities with lung cancer. Given the deep understanding of the programmed cell death-1 (PD-1)/programmed death-ligand 1 (PD-L1) pathway in cancer immunity and the successful application of immune checkpoint inhibitors (ICIs) in lung cancer, recent studies have noticed the role of the PD-1/PD-L1 axis in IPF. However, the conclusions are ambiguous, and the latent mechanisms remain unclear. In this review, we will summarize the role of the PD-1/PD-L1 axis in IPF based on current murine models and clinical studies. We found that the PD-1/PD-L1 pathway plays a more predominant profibrotic role than its immunomodulatory role in IPF by interacting with multiple cell types and pathways. Most preclinical studies also indicated that blockade of the PD-1/PD-L1 pathway could attenuate the severity of pulmonary fibrosis in mice models. This review will bring significant insights into understanding the role of the PD-1/PD-L1 pathway in IPF and identifying new therapeutic targets.